Afinal, o que é pseudonotícia? : um estudo sobre o The i-Piauí Herald, O Sensacionalista e o Laranjas News - Gerson, Deborah Cattani (2014)
This work focuses on the investigation and definition of fake news as well as on how journalistic parody occurs in Brazil. So as to accomplish this objective, the sites The i-Piuaí Herald, Sensacionalista and Laranjas News were observed. Through a literature review, based on humor, entertainment and the philosophy of language, this dissertation concentrates on the understanding of the practice of this not so new communication niche. As a bibliographical work, this research relies on a multidisciplinary approach to address this issue as well as to unveil what has not yet been brought to light by other researchers. For this purpose, concepts by authors such as Bakhtin (1992, 1993), Marcondes Filho (2004), Marcondes (2012), Young (2013), Vázquez (1999), Lipovetsky (1983, 2011) and Alberti (1999) were applied. This work promotes a debate on what news is, what it represents and stands for and how it can be transformed in products of humor. Results of this contente analysis showed that the use of irony, deliberate error and analogy are common in the production of fake news. Furthermore, the production of this type of communication product is very similar to the journalistic process of newsmaking, supporting the application of the categories of news value and decision making in this academic research.